2021
DOI: 10.24018/ejbio.2021.2.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Resistance Profiles of Pathogenic Escherichia coli in Uganda

Abstract: Escherichia coli has been implicated as one of the main etiological agents of diarrhea, urinary tract infections, meningitis and septicemia worldwide. The ability to cause diseases is potentiated by presence of virulence factors. The virulence factors influence the capacity of E. coli to infect and colonize different body systems. Thus, pathogenic E. coli are grouped into DEC strains that are mainly clustered in phylogenetic group B1 and A; ExPEC belonging to A, B2 and D. Coexistence of virulence and beta-lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Furthermore, resistance to last-resort antibiotics used in treating multidrug-resistant (MDR) infections has been reported worldwide ( Centre for Disease Dynami, 2015 ). For example, several studies have reported a high prevalence of carbapenem resistance in Uganda ( Ssekatawa et al, 2018 ; Ssekatawa et al, 2021a ; Ssekatawa et al, 2021b ), yet carbapenems are a class of antibiotics earmarked to treat MDR gram-negative bacterial infections. Thus, resistance to carbapenems limits the treatment options for MDR infections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, resistance to last-resort antibiotics used in treating multidrug-resistant (MDR) infections has been reported worldwide ( Centre for Disease Dynami, 2015 ). For example, several studies have reported a high prevalence of carbapenem resistance in Uganda ( Ssekatawa et al, 2018 ; Ssekatawa et al, 2021a ; Ssekatawa et al, 2021b ), yet carbapenems are a class of antibiotics earmarked to treat MDR gram-negative bacterial infections. Thus, resistance to carbapenems limits the treatment options for MDR infections.…”
Section: Introductionmentioning
confidence: 99%